Enzymatic activity profile of a Brazilian culture collection of Candida albicans isolated from diabetics and non-diabetics with oral candidiasis - Sanita, Paula Volpato [UNESP]; Zago, Chaiene Evelin [UNESP]; Pavarina, Ana Claudia [UNESP]; Jorge, Janaina Habib [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2014)
The secretion of hydrolytic enzymes is a fundamental virulence factor of Candida albicans to develop disease. The objective of this study was to characterise the virulence of 148 clinical isolates of C. albicans from oral candidiasis by assessing the expression of phospholipase (PL) and secreted aspartyl proteinase (SAP). Isolates were obtained from healthy subjects (HS) and diabetics (DOC) and non-diabetics with oral candidiasis (NDOC). An aliquot (5l) of each cell suspension was inoculated on PL and SAP agar plates and incubated. Enzymes secretion was detected by the formation of an opaque halo around the colonies and enzymatic activity (PZ) was determined by the ratio between colony diameter and colony diameter plus the halo zone. Statistical comparisons were made by a one-way anova followed by Tukey's post hoc test (=0.05). The clinical sources of C. albicans had significant effect (P<0.001) on the PZ values of both enzymes. For PL, clinical isolates from NDOC and DOC had highest enzymatic activity than those from HS (P<0.05), with no significant differences between them (P=0.506). For SAP, C. albicans from NDOC showed the lower enzymatic activity (P<0.001). There were no significant differences between isolates from HS and DOC (P=0.7051). C. albicans isolates from NDOC and DOC patients showed an increased production of PL.
Keywords: Candida albicans; phospholipase; secreted aspartyl proteinase; oral candidiasis; diabetes mellitus